Perioperative nutritional assessment and interventions in patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC): A systematic review. Issue 5 (May 2023) - Gearing, Peter F.; Hawke, Justin A.; Mohan, Helen; Heriot, Alexander G.; Khan, Ayman; Beaumont, Anna; Laing, Erin; Waters, Peadar S.
Abstract: Background: Peritoneal carcinomatosis is a catabolic state and cytoreductive surgery (CRS) is a high morbidity operation. Optimising perioperative nutrition is crucial to improve outcomes. This systematic review sought to examine literature describing clinical outcomes related to preoperative nutrition status and nutrition interventions in patients undergoing CRS with hyperthermic intraperitoneal chemotherapy (HIPEC). Methods: A systematic review was registered with PROSPERO (300326). A search of eight electronic databases was undertaken on 8th May 2022 and reported according to the PRISMA statement. Studies reporting nutrition status through use of screening and assessment tools, nutrition interventions or nutrition-related clinical outcomes for patients undergoing CRS with HIPEC were included. Results: Of 276 screened studies, 25 studies were included for review. Commonly used nutrition assessment tools for CRS-HIPEC patients included Subjective Global Assessment (SGA), sarcopenia assessment with computed tomography, preoperative albumin, and body mass index (BMI). Three retrospective studies compared SGA with postoperative outcomes. Malnourished patients were more likely to have postoperative infectious complications (p = 0.042 SGA-B, p = 0.025 SGA-C). Malnutrition was significantly associated with increased hospital length of stay (LOS) in two studies (p = 0.006, p = 0.02), and with overall survival in another study (p = 0.006). Eight studies analysing preoperative albumin levels reported conflicting associations with postoperative outcomes. BMI in five studies was not associated with morbidity. One study did not support routine nasogastric tube (NGT) feeding. Conclusions: Preoperative nutritional assessment tools, including SGA and objective sarcopaenia measures, have a role in predicting nutritional status for CRS-HIPEC patients. Optimisation of nutrition is important for preventing complications.